Social Values Analysis Toward Ecotourism Development in The Kei Islands - Jamaludin Kabalmay; Ricky Avenzora; Dudung Darusman; Nimmi Zulbairnarni (Institut Pertanian Bogor (IPB University), 2022)
The application of carrying capacity has the potential to protect tourist areas, both natural and cultural, and it is also related to the lifestyle of the local community, as well as the potential of tourist destinations. The condition of the people of the Kei Islands who are still experiencing conflicts of interest in several areas causes a development that is not according to plan or can even change or destroy the character of natural and cultural resources. The purpose of this study was to analyze the condition of social values ​​related to current social carrying capacity with conditions 10 years ago. The number of respondents was 600 people who come from 10 community groups. Primary data were obtained through filling out a list of questions by respondents using a closed-ended questionnaire by applying the “one score one indicator scoring system”. Data analysis was carried out in a quantitative descriptive manner based on the average value of each indicator. To find out the difference between the current condition and the condition 10 years ago, a paired t test was conducted. The results showed that the local community's response to tourism development activities both now and 10 years ago felt positive and negative impacts. The conditions of social situations that produce positive impacts are condusive situations, associations, cooperative situations, and productive collaborations, while the negative ones were dissociation, conflict, and war. Communication and economic aspects must be the attention of the parties so that conflicts of interest can be reduced so that the development of ecotourism in the Kei Islands can be more optimal.